Wheelchairs with adjustable motorised kit for the elderly - UMP, PNC (2019)
Two Universiti Malaysia Pahang (UMP) lecturers had come up with an adjustable motorised kit for wheelchair that would provide better mobility for the elderlies and handicapped.